THE ISSUE OF POETIC SYNTAX IN THE WORK OF A YOUNG POET (ANALYSIS OF THE POETRY COLLECTION JAZBA) (World Bulletin of Social Sciences, 2024)
This article examines several poems from the collection Jazba by the contemporary young poet Jontemir Jondor. It explores themes such as homeland, freedom, nature, and love as depicted in his works. The study highlights the language of artistic imagery, poetic expressions, and the intertwining of time and space within his modernist creative framework.